Reliability and Validity Testing of the Quality of Life in Late-Stage Dementia Scale. Issue 5 (August 2018) - Resnick, Barbara; Galik, Elizabeth; Kolanowski, Ann; Van Haitsma, Kimberly; Boltz, Marie; Ellis, Jeanette; Behrens, Liza; Flanagan, Nina M.
Background/rationale: This study tested the psychometric properties of the Quality of Life in Late-Stage Dementia (QUALID) Scale using Rasch analysis. The QUALID includes 11 items with a 5-point response scale. Scores range from 11 to 55, and lower scores indicate higher quality of life (QoL). Methods: Baseline data from a randomized clinical trial including 137 residents from 14 nursing homes were used. Psychometric testing included item mapping, evaluation of response categories, item reliability, construct validity based on INFIT and OUTFIT statistics, and convergent validity based on correlations between QoL and pain, agitation, depression, and function. Results: The Cronbach α was .89. All the items except "appears physically uncomfortable" fit the model. There was a significant relationship between QoL and depressive symptoms ( r = .71, P = .001), pain ( r = .26, P = .01), physical function ( r = −.19, P = .03), and agitation ( r = .56, P = .001). The categories were appropriately used. Item mapping suggested a need for easier items.